Influence of Lymphocyte T CD4 Levels on the Neuropsychological Performance of Population Affected by HIV and with a Previous History of Substance Use - Vázquez-Justo, Enrique; García-Torres, Amalia; Vergara-Moragues, Esperanza (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
The immunological markers help to know if there is a good recovery of the immunological system in patients infected with HIV. Among them, the lymphocyte T CD4 rate is the main indicator of the patient’s immunological state being used for staging HIV infection, evaluating the mortality or comorbidity risk and the vulnerability to certain oportunistic infections. However, its link with the presence of cognitive alterations is not clear. Therefore, the aim of this article is to study if lymphocyte T CD4 levels are connected with the neuropsychological performance of a group of people infected with HIV and with a previous history of substance use. The sample consisted of 80 seropositive males with a previous history of substance use. They were evaluated by means of a neuropsychological battery which assesses the most affected cognitive domains in HIV population. The results showed that the patients having a higher level of immunodeficiency (CD4 <200/ mm3) have a poorer performance in terms of attention, visuomotor dexterity, visual memory, visual perception, auditory-verbal learning and inhibition. Therefore, our results show a realtion between the lymphocyte T CD4 rate and the neuropsychological performance in seropositive people with a previsous history of substance use.
Keywords: evaluation; medicine; neuropsychological; HIV; IJIMAI